Natural History of Rasmussen’s Syndrome - J Gordon Millichap (Pediatric Neurology Briefs)
Seizure frequency, degree of hemiparesis and cerebral hemiatrophy are analysed in 13 patients with histopathologically proven Rasmussen’s encephalitis (RE) examined at the University of Bonn, Germany.